Subcutaneous insulin B:9-23/IFA immunisation induces Tregs that control late-stage prediabetes in NOD mice through IL-10 and IFNγ - Fousteri, G; Dave, A; Bot, A; Juntti, T; Omid, S; von Herrath, M (Diabetologia, 2010)
Aims/hypothesis Subcutaneous immunisation with the 9-23 amino acid region of the insulin B chain (B:9-23) in incomplete Freund's adjuvant (IFA) can protect the majority of 4- to 6-week-old prediabetic NOD mice and is currently in clinical trials. Here we analysed the effect of B:9-23/IFA immunisation at later stages of the disease and the underlying mechanisms. Methods NOD mice were immunised once s.c. with B:9-23/IFA at 5 or 9 weeks of age, or when blood glucose reached 10 mmol/l or higher. Diabetes incidence was followed in addition to variables such as regulatory T cell (Treg) induction, cytokine production (analysed by Elispot) and emergence of pathogenic CD8⁺/NRP-V7⁺ cells. Results A single B:9-23/IFA immunisation protected the majority of NOD mice at advanced stages of insulitis, but not after blood glucose reached 13.9 mmol/l. It increased Treg numbers and lost its protective effect after IFNγ or IL-10 neutralisation, but not in the absence of IL-4. CD4⁺CD25⁺ and to a lesser extent IFNγ-producing cells from mice protected by B:9-23/IFA induced tolerance upon transfer into new NOD animals, indicating that a dominant Treg-mediated effect was operational. Reduced numbers of CD8⁺/NRP-V7⁺ memory T cells coincided with protection from the disease. Conclusions/interpretation Protection from diabetes after B:9-23/IFA immunisation cannot be achieved once diabetes is fully established, but can be achieved at most prediabetic stages of the disease. Protection is mediated by Tregs that require IFNγ and IL-10. These findings should provide important guidance for ongoing human trials, especially for the development of suitable T cell biomarkers.